Why I Continue to Support Community Water Fluoridation - Herschel S. Horowitz, DDS, MPH (Blackwell Synergy, 2000)
In 1997 the journal Perspectives in Biology and Medicine published an article by John Colquhoun entitled ÃƒÂ¢Ã¢â€šÂ¬Ã‚ÂWhy I changed my mind about water fluoridationÃƒÂ¢Ã¢â€šÂ¬Ã‚Â (1). Colquhoun had served as the principal dental officer for the city of Auckland, New Zealand, in the 1970s and early 1980s